Comparison of hospital‐based and hospital‐based home care at diabetes onset in children. Issue 3 (November 2014) - Tiberg, I; Hallström, I; Jönsson, L; Carlsson, A
Abstract The aim was to compare two different regimens for children diagnosed with type 1 diabetes, hospital‐based care and hospital‐based home care (HBHC), in terms of the child's metabolic control, episodes of severe hypoglycaemia, the disease's impact on family and the parents' health‐related quality of life, one year after diagnosis. The study had a randomised controlled design and included 60 children, aged 3–15 years old. Children were randomised to either continued hospital‐based care or to HBHC. This article presents data one year after diagnosis. The results showed overall equivalence between groups. There were no differences in terms of the children's HbA1c (p=0.804), in episodes of severe hypoglycaemia (p=1.0), in insulin dose/kg/24 h (p=0.115) or parents reported impact of the child's disease on the family (p=0.163). However, parents in the HBHC showed significant higher social functioning compared to parents in the hospital‐based care (p=0.006). In conclusion, few studies provide high‐quality evidence when comparing hospital‐based care with different models of home‐based care. The results of this study one year after diagnosis support the safety and feasibility of HBHC when a child is diagnosed with type 1 diabetes.